Simulation of multicentric destruction with regard for inhomogeneous distribution of rated voltage - Vitaly F. Lukyanov (Advanced Engineering Research, 2015)
The algorithm simulating the initiation and development of fatigue cracks in the joint weld on the example of the mount of the mobile platform and the supporting cowl of Gottwald NMK 170 EG (63 tons) crane rotator, the destruction of which occurred in 2011 in the territory of “Novorossiysk commercial sea port” OJSC (NCSP), is worked out. The proposed algorithm takes into account the non-uniform weld geometry affecting the value of the stress concentration factor and the uneven distribution of the rated stress related to the joint design features. The modeling process is based on the experimentally established fact that the geometry profile of the junction between the weld and the base metal along the welded joint changes randomly. As a result, the fatigue flaking along the weld lacks any regular pattern. Under the cyclic loading, the development of the destruction is a sequential process of the crack nucleation in different parts of welded joints along the weld, single surface cracks growth under the fracture mechanics laws, nucleation of new cracks, and crack coalescence in the adjoining sections. At the coalescence of the crack edges, the contour profile is changing which leads to increasing the growth rate of the crack depth. In the future, the development of the multicentric destruction continues until the critical crack. The damage accumulation and destruction development rate depends on the uniformity coefficient of the stress concentration along the weld. The implementation of the proposed model allows solving the problems of determining the frequency of node diagnosis and the points with the utmost probability of fatigue cracks initiation, as well as validating the possible methods of structural reinforcement.